1995
DOI: 10.1099/00222615-42-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Free secretory component and lactoferrin of human milk inhibit the adhesion of enterotoxigenic Escherichia coli

Abstract: Summary. The non-immunoglobulin component of human milk responsible for the inhibition of Escherichia coli cell adhesion (haemagglutination) mediated by colonisation factor antigen 1 (CFAl) was determined by chromatographic fractionation of human whey proteins with Sephadex G-200, DEAE cellulose and heparin-sepharose. Pure free secretory component (fSC) and pure lactoferrin (Lo were isolated and both compounds inhibited the haemagglutination induced by E. coli CFAl+. The lowest concentrations of purified fSC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 43 publications
2
81
0
Order By: Relevance
“…Adhesion of the strain possessing CFA I fimbriae, was inhibited by both, whole milk and NIgF, but not by the IgF, indicating the importance of NIgF on the adhesion of CFA I strains. These findings are corroborated by our previous studies (15,25), showing that lactoferrin and fSC present in the NIgF inhibit bacterial adhesion to erythrocytes, binding to bacterial fimbriae.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Adhesion of the strain possessing CFA I fimbriae, was inhibited by both, whole milk and NIgF, but not by the IgF, indicating the importance of NIgF on the adhesion of CFA I strains. These findings are corroborated by our previous studies (15,25), showing that lactoferrin and fSC present in the NIgF inhibit bacterial adhesion to erythrocytes, binding to bacterial fimbriae.…”
Section: Discussionsupporting
confidence: 81%
“…It has been shown that fSC is an 80 kDa glycoprotein, consisting of a single polypeptide chain largely glycosilated (20%) (19). There is little information about the role of fSC in secretions, but some workers suggest that it may have a protective role against diarrhea (4,15). Recently, using immunogold labeling, we showed the ability of fSC to interact with CFA I and CFA II (CS1 and CS3) fimbrial adhesins (25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies have demonstrated the protective effects of fucosylated oligosaccharide fractions of human milk against heat stable enterotoxin of Escherichia coli in suckling mice (10). Clostridium difficile binds to glycosylated SC to a much greater extent than to the deglycosylated form (11), and the SC-dependent inhibition of adhesion of enterotoxic forms of E. coli to erythrocytes is apparently reliant on the carbohydrate portion of SC (12). Furthermore, removal of N-linked oligosaccharides from sIgA has been shown to enhance the fixation of C3b and activation of the alternative complement pathway (3).…”
Section: S Ecretory Component (Sc)mentioning
confidence: 99%
“…Binding to E. coli colonization factors [36] causes inhibition of hemagglutination [37] and inhibition of adherence of ETEC to epithelial cells in vitro and to intestinal mucosa of germfree mice in vivo [38].…”
Section: Enterotoxigenic Escherichia Coli (Etec)mentioning
confidence: 99%